LEGAL CERTAINTY IN EVIDENCE MANAGEMENT AND CRIME-PROVED ASSETS - Amellia Dhini Pangestu; Rizki Setyobowo Sangalang; Claudia Yuni Pramita; Yurika Fahliany Dewi (RADJA PUBLIKA, 2026)
Study This analyze in a way normative arrangement law about management goods evidence and assets results crime in regulation applicable laws and regulations as well as evaluate its suitability with principle certainty law . The study was conducted through study law normative with approach legislation and conceptual , using material primary law in the form of the Criminal Procedure Code and laws sectoral related ( including the Corruption Eradication Law , the Money Laundering Law, and the Narcotics Law ), as well as material law secondary in the form of literature and articles scientific . Research results show that arrangement management goods evidence and assets results crime has provide base legality action confiscation , storage , return and seizure , including protection to party third party in good faith good . However , the settings are spread out in a number of regime law show trend potential fragmentation of norms cause difference interpretation and application . In perspective theory certainty law , condition the confirm the need harmonization and strengthening integration arrangements so that norms are more consistent , easy predicted, as well as give clear guidelines​ for enforcer law and parties interested .